STEM in Elementary School: How it impacts students’ life skills? - Gumilang, Eva Sri; Khoerulloh, Hilmi; Lubay, Lukmannul Haqim; Budiana, Dian (Universitas Pendidikan Indonesia, 2023)
The learning approach that provides experiences and abilities to support future life related to the Internet of Things (IoT) is one of the STEM approaches. This research aims to determine the effects of the STEM approach on the development of students' life skills in elementary school. The method used a quasi-experimental design with a pretest-posttest control group design, and the sample was selected through purposive sampling. The instrument used for assessing life skills was the Life Skills Scale for Sport (LSSS) developed by Cronin Allen. The results of the analysis showed a significance level of 0.002 for life skills. It can be concluded that the STEM learning approach has an impact on the development of life skills in elementary school. This can be considered an alternative for Physical Education teachers in elementary schools to instil life skills from an early age and to foster the development and reinforcement of integration in applying knowledge into skills.